Visualization Mapping Approaches for Developing and Understanding OER - Connolly, Teresa (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
Open educational resources (OER) can be described in numerous ways (Creative Commons, 2012). In this visualization based context, however, OER can be defined as …teaching, learning and research resources that reside in the public domain or have been released under an intellectual property license that permits their free use or re-purposing by others. Open educational resources include full courses, course materials, modules, textbooks, streaming videos, tests, software, and any other tools, materials or techniques used to support access to knowledge. (Hewlett Foundation, 2007) This definition emphasizes some of the aspects highlighted in this article, namely that an OER approach has also been taken to capture and visualize OER materials. In addition reference is made to the forthcoming paper, “How Diagrams Aid Teaching and Learning in STEM Subjects as Exemplified by the Teaching and Learning of Systems Thinking in Practice” (Lane, 2012, in press), which outlines how the educational process often involves a mediated discourse between teachers and learners to aid sense or meaning for both parties.